Feasibility study and carrying capacity of Lake Batur ecosystem to preserve tilapia fish farming in Bali, Indonesia - I WAYAN BUDIASA; I GUSTI NGURAH SANTOSA; I GUSTI AGUNG AYU AMBARAWATI; I KETUT SUADA; I NYOMAN SUNARTA; NATALIYA SHCHEGOLKOVA (Biodiversitas Journal of Biological Diversity, 2018)
Budiasa IW, Santosa IGN, Ambarawati IGAA, Suada IK, Sunarta IN, Shchegolkova N. 2018. Feasibility study and carrying capacity of Lake Batur ecosystem to preserve tilapia fish farming in Bali, Indonesia. Biodiversitas 19: 613-620. Lake Batur in Bangli District was potential for fishery development up to 5% of the total water area. Currently the lake area used for fishery was only 6.28 ha, leaving the area up to 77.07 ha potential for fishery development. Tilapia (Oreochromis niloticus) was the most abundant fish in the lake. This research aimed to evaluate the financial feasibility of tilapia fish farming with Floating Net Cages (FNC) technology within the lake and to assess its carrying capacity for the tilapia aquaculture. Discounted investment criteria were used to test farm survey data from 30 tilapia fish growers at top three villages which had the largest number of FNC. Six water samples were taken using deep water sampler at three sampling points were analyzed to see a number water chemistry and physics condition. The results showed that economic life of a FNC was financially feasible as indicated by the positive Net Present Value (NPV), Internal Rate of Return (IRR) was greater than 9% and Net Benefit Cost Ratio (Net B/C) was greater than one; and however the water quality as indicated by value of TDS, NO2, BOD, Total-P, NH3, and P-PO4 exceeded the maximum limit of water quality criteria class II based on Government of Indonesia Regulation No. 82/2001. Thus, FNC should not be more expanded within the lake due to water pollution of the lake.